Stedssensitive interviews - Sand, Anne-Lene (Tidsskrift for Professionsstudier, 2019)
The purpose of the article is to rethink interviews methods through an attention to where the interview takes place and through this develop interview method that nuance sensory aspects of practices. Through Michel de Certeau’s anthropological understanding of everyday practices, a place-sensitive perspective, inspired by place phenomenologist Edwards Casey and anthropologist Sarah Pink’s concept of emplacement, the article reflects and explore what these concepts make us achieve when it comes to constructing a deeper understanding for practices. The article analyzes empirical material of an interview situation and argues that sensory aspects of practice can be generated through a place-sensitive interview. The author points at a tendency within interview methodology where the place of the interview often is understood and treated as tabula rasa and reduced to considerations of convenience and comfort. This tendency reveals an insufficient methodological recognition of the significance of place for interview knowledge constructions. Based on an empirical material generated in an ethnographic field work, the article nuances how researchers can activate his body and senses in interview contexts, create concrete grasp of place and at the same time ask practice specific questions in situ. The article aims towards professionals who work with interviews as methodological approach and the author of the article calls for place to be the subject of reflection, on equal level with interview dimensions such as questions and ethics.